Fluoride content of locally available edible seaweeds A preliminary Study - Chua, Joselyn; Chung, Rosanna; Estaniel, Cynthia (Adviser).
It had been proven already that fluoride reduces the susceptibility of the teeth to caries and periodontal problems. Therefore, different vehicles were proposed and tested to extend the dental benefits of fluoride. Unfortunately, those people living in the remote coastal areas have less access to these. In order to extend the dental benefits of fluoride, we did an investigation on the presence of fluoride among locally available edible seaweeds. Because recently, the gathering of seaweeds in the Philippines has been greatly encouraged due to its uses for pharmaceutical preparations and medicinal purposes, It has been noted also that majority of the people living near the sea have seaweeds as part of their diet. Indeed, we were able to find out that locally available edible seaweeds have fluoride. The edible seaweeds investigated were the following: Gelidiella acerosa, Eucheuma spinosum, Gracilaria verrucosa, Gracilaria Salicornia, Codium edule, Eucheuma striatum and Caulerpa lentillifera.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Marine algae; Fluorides